Decentralizing the Governance of Inland Fisheries in the Pacific Region of Colombia. Issue 1 (30th May 2022) - Ocampo-Diaz, Natalia; Lopez, Maria Claudia; Axelrod, Mark; Norris, Patricia
In 1993, Colombia launched a decentralization process granting Black communities collective property rights over territories they had inhabited for centuries. Decentralization was intended to promote inclusive governance, enhance environmental governance in Black communities' territories, and reduce poverty. This paper presents a qualitative case study of decentralized inland fisheries governance in the country's largest Community Council. Our results suggest that decentralization policies need to account for particularities of resource systems and community dynamics. Inland fisheries governance poses specific challenges for decentralization because a) ecological dynamics supporting the resource system take place beyond the administrative boundaries of fisheries; b) rivers are public goods in Colombia, and therefore it is impossible to exclude users from accessing them; and c) regulations are not well-enforced in places where fish are sold. This calls for a combined effort from stakeholders with different rights, duties, and capacities within the governance system to coordinate actions for enforcing regulations.